PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI PADI (Oryza sativa) DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Made Indra Murdani; Sudarma Widjaya; Novi Rosanti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The purposes of this research were to analyze the income of paddy farmer households, the expenditure of paddy farmer households, and the level of paddy farmer household’s welfare. This research was conducted at Yogyakarta village of Gadingrejo subdistrict of Pringsewu regency. The samples were chosen by simple random sampling method. The number of respondents in this study was 68 paddy farmers. The data was collected in June-July 2014. The method of data analysis used in this study is quantitative and qualitative descriptive analysis. The results showed that the income of paddy farmers at Yogyakarta village was Rp19,590,645.92 per year obtained from Rp11,292,223.13 per year (57.64%) of the paddy farm, Rp5,748,422.79 per year (29.34%) of the farm in addition to paddy and the income from outside the farm was Rp2,550,000.00 per year (13.02%). The expenditure of paddy farmer households at Yogyakarta village was Rp17,980,227.94 per year obtained from Rp10,818,970.59 per year or (60.17%) of the expenditure for foods, and Rp7,161,257.35 per year (39.83%) of the expenditure for nonfoods.  Based on the criteria of Sajogyo (2007) paddy farmer ‘s households at Yogyakarta village of Gadingrejo subdistrict of Pringsewu Regency, 37 (54,41%) were categorized as prosperous farmer households and 31 (45.59%) farmer households were categorized as economically enough. Key words: paddy farmers, income, farmer household’s welfare, Pringsewu, Indonesia